Impact of incremental circumferential resection margin distance on overall survival and recurrence in oesophageal adenocarcinoma. Issue 4 (23rd April 2018) - Knight, W R C; Zylstra, J; Wulaningsih, W; Van Hemelrijck, M; Landau, D; Maisey, N; Gaya, A; Baker, C R; Gossage, J A; Largergren, J; Davies, A R
Abstract: Background: Previous analyses of the oesophageal circumferential resection margin (CRM) have focused on the prognostic validity of two different definitions of a positive CRM, that of the College of American Pathologists (tumour at margin) and that of the Royal College of Pathologists (tumour within 1 mm). This study aimed to analyse the validity of these definitions and explore the risk of recurrence and survival with incremental tumour distances from the CRM. Methods: This cohort study included patients who underwent resection for adenocarcinoma of the oesophagus between 2000 and 2014. Kaplan–Meier and Cox regression analyses were performed to determine the hazard ratio (HR) with 95 per cent confidence intervals for recurrence and mortality in CRM increments: tumour at the cut margin, extending to within 0·1–0·9, 1·0–1·9, 2·0–4·9 mm, and 5·0 mm or more from the margin. Results: A total of 444 patients were included in the study. Kaplan–Meier and unadjusted analyses showed a significant incremental improvement in overall survival ( P < 0·001) and recurrence ( P for trend < 0·001) rates with increasing distance from the CRM. Tumour distance of 2·0 mm or more remained a significant predictor of survival on multivariable analysis (HR for risk of death 0·66, 95 per cent c.i. 0·44 to 1·00). Multivariable analysis of overall survival demonstrated a significant difference between a positive and negative CRM with the Royal College of Pathologists' definition (HR 1·37, 1·01 to 1·85), but not with the College of American Pathologists' definition (HR 1·22, 0·90 to 1·65). Conclusion: This study demonstrated an incremental improvement in survival and recurrence rates with increasing tumour distance from the CRM. Graphical Abstract: This study suggests that circumferential resection margin (CRM) distance positively influences survival and recurrence incrementally as tumour is found from the cut margin, with the Royal College of Pathologists' definition being an independent risk factor of poor survival. This study also identifies a further 'at risk' CRM category of 1–2 mm. This study found that adverse prognostic variables also decrease incrementally away from the cut margin suggesting it may be more helpful to consider CRM distance as a proxy marker of the aggressive nature of oesophageal adenocarcinoma. Small distances make a difference